The Role of Aquaculture in Shaping the Morphology of Babylonia areolata: A Comparative Study of Cultured and Wild Populations - Haishan Wang; Zhi Chen; Yuhe Tong; Le Ye; Youming Li (Biology)
Background: With the rapid expansion of aquaculture, the impact of rearing environments on the morphological characteristics of marine species has become a critical research focus. This study investigates the morphological differences between wild and cultured populations of B. areolata, a commercially valuable marine mollusk, to understand how aquaculture environments influence morphological traits. Objective: The study aims to evaluate the morphological variance between wild and cultured populations using multivariate statistical techniques and to analyze the ecological implications of these differences. Methods: A total of 120 specimens (56 cultured, 64 wild) were collected from 2 habitats in Hainan, China, and analyzed for 9 morphological traits. Statistical methods, including Principal Component Analysis (PCA) and Linear Discriminant Analysis (LDA), were used to assess morphological differences. Results: The study revealed significant morphological differences between wild and cultured populations of B. areolata. Cultured populations exhibited greater morphological uniformity, particularly in traits such as shell height, shell length, and total weight. In contrast, wild populations showed higher variability in traits like shell thickness and shell aperture width, driven by resource heterogeneity and natural selection pressures in their environment. Conclusion: The findings suggest that aquaculture environments significantly influence the development of morphological traits, potentially affecting mollusk adaptability and survival in natural habitats. These results provide valuable insights into aquaculture management and strategies for conserving wild populations.